Uncommon Cause of Right Upper Quadrant Pain Treated by Laparoscopic Surgery: A Case Report - Feng, Qingbo; Du, Jinpeng; Liao, Wenwei; Zheng, Jinli; Zeng, Yong; Li, Jiaxin (Frontiers in Surgery, 2022)
Abstract Introduction: Right upper quadrant pain is a very common symptom of cholecystitis. Right upper quadrant pain caused by fish bone perforation of stomach wall is rare. Case Presentation: We report a 42-year-old woman who was admitted to our hospital with “1-month history of dull progressive right upper quadrant pain radiating to the back”. Computed tomography of the abdomen revealed a linear, high-density body between the stomach wall and the liver. On history, the patient stated she had eaten a bony fish a month prior but didn’t note any significant pain at the time. Laparoscopy revealed a fish bone 2 cm in length half on the surface of liver caudal lobe, and no perforation of gastrointestinal tract was found. The postoperative course was uncomplicated, and the patient discharged home on day 3 after surgery. Conclusion: The case of right upper quadrant pain caused by the fish bone is very rare. Radiological examinations play a significant role in the diagnosis of fish bone ingestion. Laparoscopic surgery is technically feasible and safe for the treatment of patients with fish bone ingestion.